High mobility field-effect transistors with versatile processing from a small-molecule organic semiconductor - Mei, Yaochuan (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.